Realizing Good Local Governance Through Local Government Apparatus Empowerment Strategy - Lay, Marthina Raga; Daeng, Ernawati; J.Therik, Jeni (International Journal Labs, 2023)
Changes in the paradigm of governance in the implementation of regional autonomy, have made regional governments the spearhead in the implementation of government tasks, especially in providing services to the community.as a consequence of these changes, it is necessary to rearrange various elements in the governance system. Good local governance is the most important issue in the management of public administration today. Government apparatus resources are a vital and strategic element in the administration of government, both at the center and in the regions. In the context of local governance, the performance of local government apparatus resources needs to be continuously improved. The increase is closely related to the development and development of the role of government officials as civil servants (PNS). For this reason, the right strategy is needed to empower the resources of the local government apparatus which includes efforts to make the competencies of the government apparatus so that they can be used optimally in realizing good local governance.